School wellness policy strength, nutrition-related behaviors, and weight outcomes among high school students: an ecological study - Olson, Ryhan M. (My University, 2025)
Background: Adolescent health-related behaviors are less than ideal, and 1 in 3 adolescents in the U.S. is affected by overweight or obesity. The rates of overweight and obesity, as well as the behavioral risk factors associated with these conditions, vary by state. An improved understanding of the relationship between policy, health-related behaviors, and statewide weight outcomes is needed to inform public health strategies and programming. Objective: To determine the association between school wellness policy strength, statewide health-related behaviors, and statewide weight outcomes among high school students. Methods: Using an ecological study design, state-level data on overweight and obesity, fruit and vegetable consumption, soda consumption, and physical activity were collected from the Youth Risk and Behavior Surveillance Survey of high school students in 2023. Using the National Cancer Institute’s 2022 Classification of Laws with School Students, a total policy score was calculated for each state using physical education and nutrition law scores. Pearson correlation analyses were used to measure the relationship between policy strength, statewide health-related behaviors, and statewide weight outcomes. Results: Statewide combined rates for overweight and obesity ranged from 25.8% ─ 39.3%. Vegetable consumption (r = −.84, p < .001), fruit consumption (r = −.59, p = .001), and physical activity (r = −.38, p = .038) were negatively correlated with the combined rate of overweight and obesity. Soda consumption was positively correlated (r = .78, p < .001) with the combined rate of overweight and obesity. Policy scores ranged from 0 to 15. Obesity (r = .38, p = .024), overweight (r = .415, p = 0.013), overweight and obesity (r = .47, p = .004), and soda consumption (r = .41, p = .029) were positively correlated with policy scores. Vegetable onsumption which was negatively correlated with policy strength (r = - .62, p = .002) was the only health behavior variable significantly correlated with policy. Conclusion: Higher statewide rates of fruit consumption, vegetable consumption, physical activity and lower rates of soda consumption were associated with lower rates of overweight and obesity. While overall state policy strength was not associated with improved weight or health behavior outcomes, these findings suggest that a continued emphasis should be placed on increasing these healthful behaviors in public efforts to shape adolescent weight outcomes.
Keywords: Obesity and overweight; Adolescents; Policy; Fruit and vegetable consumption; Soda consumption; Physical activity